Unconventional Secretion, Gate to Homeoprotein Intercellular Transfer - Joliot, Alain; Prochiantz, Alain (Frontiers in Cell and Developmental Biology, 2022)
Unconventional secretion allows for the secretion of fully mature and biologically active proteins mostly present in the cytoplasm or nucleus. Besides extra vesicle-driven secretion, non-extravesicular pathways also exist that specifically rely on the ability of the secreted proteins to translocate directly across the plasma membrane. This is the case for several homeoproteins, a family of over 300 transcription factors characterized by the structure of their DNA-binding homeodomain. The latter highly conserved homeodomain is necessary and sufficient for secretion, a process that requires PI(4,5)P2 binding, as is the case for FGF2 and HIV Tat unconventional secretion. An important feature of homeoproteins is their ability to cross membranes in both directions and thus to transfer between cells. This confers to homeoproteins their paracrine activity, an essential facet of their physiological functions.